A mechanical model for shear design of steel fiber reinforced concrete beams without shear reinforcements. (June 2021) - Bi, Jihong; Wang, Zhaoyao; Zhao, Yun; Huo, Linying; Xie, Yuhang
Abstract: A number of models have been proposed to estimate the shear strength of steel fiber reinforced concrete (SFRC) beams. Nevertheless, the previous models have not been widely accepted in terms of consistency and applicability. This study presents a mechanical model to estimate the shear strength of SFRC slender beams without shear reinforcements. The basic assumptions of the proposed model are agreeable with that of the Critical Shear Crack Theory (CSCT), which has been effectively verified by extensive experimental measurements. The calculation of shear strength considers the contributions of various shear-resisting mechanisms, including the shear resistance provided by the compression zone, residual tensile strength and dowel action in main reinforcements, while neglecting the shear resisted by the aggregate interlock. To obtain the shear resistance provided by residual tensile stress along the critical shear crack and determine the neutral axis depth, a compact constitutive law is presented for the residual tensile stress of SFRC with determined crack width. The impact of steel fibers on each shear-transfer action is studied and considered in the formula of each shear-resisting mechanism. The proposed mechanical model can estimate the shear strength of SFRC slender beams without shear reinforcements, the deformation capacity and the location of the critical shear crack. For design purposes, a simplified model is also presented considering the relation between various shear-resisting mechanisms and critical shear crack. The accuracy of mechanical model and simplified model is extensively verified by comparing predicted values of proposed models and previous eight models with experimental data of the two databases.